ANALYSIS OF LEARNING IMPLEMENTATION PLAN AT X BIOLOGY CLASS IN SMA AND MA BABAT DISTRICT - Zulfia, Firda Ama; Yunanda, Intan; Mawaddah, Kuni (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.527, 2017)
The learning implementation plan is the teaching guide used by the teacher during the learning process. The lesson plan will assist the teacher in organizing the standard materials, as well as anticipating learners and the problems that may arise in the lesson. Learning implementation plans usually make by the teacher of each subject for their guidance in carrying out the lesson. Based on the survey results in the field, the implementation plan of learning used by the teacher is not necessarily in accordance with the components of the implementation plan of learning listed in permendikbud number 22 of 2016 on Standard and Basic Education Process Standards. The purpose of this study was conducted to determine the suitability of the implementation plan of learning that used the classroom biology teachers of  X class in SMA and MA Negeri Babat District of Lamongan Regency with the application of 2013 curriculum at 2016/2017 academic year. This research uses descriptive qualitative research method. Researcher use purposive sampling technique. The sample used is the implementation plan of learning biology X class at 2016/2017 academic year in two public schools located in Babat District namely SMA Negeri 1 Babat and MAN 2 Lamongan. Based on the results of data analysis can be seen that not all components of the learning implementation plan according to permendikbud 22 years 2016 listed in the learning implementation plan made by teachers in SMA Negeri 1 Babat and MAN 2 Lamongan.